2020
DOI: 10.15294/kemas.v15i3.20373
|View full text |Cite
|
Sign up to set email alerts
|

Integration of the Maternal Death Prevention Program based on the Health Belief Model Framework

Abstract: In 2015, the Health Office of Banyumas Regency records 7 cases of maternal deaths, 243 cases of infant deaths, and 41 cases of under-five deaths. Compared to 2015, maternal mortality increases in the first three months of 2016. This research aims to identify the causes of maternal deaths that occur in 2016 in Banyumas Regency using the Health Belief Model conceptual framework. The results show that the cause of maternal death in Banyumas Regency is the lack of antenatal services due to the lack of knowledge an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…20 , 21 Rizqi and Rubai reported that health service utilization should be considered because it is one of the determinants of receiving inappropriate care and diagnostic delays. 14 ‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬…”
Section: Introductionmentioning
confidence: 99%
“…20 , 21 Rizqi and Rubai reported that health service utilization should be considered because it is one of the determinants of receiving inappropriate care and diagnostic delays. 14 ‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬…”
Section: Introductionmentioning
confidence: 99%